Neurophysiology of Nicotine Addiction - Dani, John A. (2011)
Tobacco use is a major health problem, and nicotine is the main addictive component. Nicotine binds to nicotinic acetylcholine receptors (nAChR) to produce its initial effects. The nAChRs subtypes are composed of five subunits that can form in numerous combinations with varied functional and pharmacological characteristics. Diverse psychopharmacological effects contribute to the overall process of nicotine addiction, but two general neural systems are emerging as critical for the initiation and maintenance of tobacco use. Mesocorticolimbic circuitry that includes the dopaminergic pathway originating in the ventral tegmental area and projecting to the nucleus accumbens is recognized as vital for reinforcing behaviors during the initiation of nicotine addiction. In this neural system β2, α4, and α6 are the most important nAChR subunits underlying the rewarding aspects of nicotine and nicotine self-administration. On the other hand, the epithalamic habenular complex and the interpeduncular nucleus, which are connected via the fasciculus retroflexus, are critical contributors regulating nicotine dosing and withdrawal symptoms. In this case, the α5 and β4 nAChR subunits have critical roles in combination with other subunits. In both of these neural systems, particular nAChR subtypes have roles that contribute to the overall nicotine addiction process